The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1063/1.363806
|View full text |Cite
|
Sign up to set email alerts
|

Improved modeling of grain boundary recombination in bulk and p-n junction regions of polycrystalline silicon solar cells

Abstract: This article provides a theoretical investigation of recombination at grain boundaries in both bulk and p-n junction regions of silicon solar cells. Previous models of grain boundaries and grain boundary properties are reviewed. A two dimensional numerical model of grain boundary recombination is presented. This numerical model is compared to existing analytical models of grain boundary recombination within both bulk and p-n junction regions of silicon solar cells. This analysis shows that, under some conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…The J ( V ) relations for these cases are summarized in Table I. Similar results have been obtained in previous works on this problem 20,22 , however some of the relations we present are new. In Sec.…”
Section: Introductionsupporting
confidence: 86%
“…The J ( V ) relations for these cases are summarized in Table I. Similar results have been obtained in previous works on this problem 20,22 , however some of the relations we present are new. In Sec.…”
Section: Introductionsupporting
confidence: 86%
“…Consequently, the possibility of carbon and oxygen contamination is low because the duration for which the sheet is in contact with the mold is short. The vertically aligned grains produced via spin casting differ from the horizontal grains or random microstructures formed by other methods, with such differences having been studied by Edmiston et al 9 In present study, the bulk lifetime of the spin-cast sheets were measured by the microwave photoconductance decay (MW-PCD) techinique using a SEMILAB WTN-2000 instrument. The microstructure of the sheets was investigated thorough analysis of backscattered electron (BSE) images obtained using an electron probe microanalyzer (EMPA), while the character of the grain boundaries was determined by a setup incorporating a scanning electron microscope (SEM)/electron backscatter diffraction (EBSD)/orientation image micrograph (OIM).…”
Section: Introductionmentioning
confidence: 90%
“…on J-V characteristics) is device simulation. A number of studies on the influence of grain boundaries in silicon-based devices can be found in references [8][9][10][11][12][13]. In general, the GB is modeled as an interface layer with a specific trap density and interface recombination velocity.…”
Section: Introductionmentioning
confidence: 99%